Adverse Event Profile Differences Between Metyrapone and Osilodrostat: A Pharmacovigilance Study of the FDA Adverse Event Reporting System - Xia, Chunyong; Hu, Lanxin; Fan, Ying; Liu, Jie; Gan, Ya (Hormone and Metabolic Research, 2025)
Metyrapone and osilodrostat are both steroidogenic inhibitors targeting the 11β-hydroxylase, yet their safety profile has not been comprehensively analyzed. The objective of this study is to compare the adverse events (AEs) associated with osilodrostat and metyrapone based on the Food and Drug Administration Adverse Event Reporting System (FAERS). AEs were classified according to the System Organ Class (SOC) in the Medical Dictionary for Regulatory Activities (MedDRA) version 26.1. Adverse event (AE) signals of osilodrostat and metyrapone were determined by calculating reporting odds ratios (ROR). A total of 1380 and 449 AE reports were retrieved from osilodrostat and metyrapone, respectively, involving 26 and 27 SOC categories. Unexpected AEs such as asthenia, decrease of blood potassium, myalgia, increase of blood pressure, abdominal distension, increase of blood testosterone, nephrolithiasis, and hunger were associated with osilodrostat. while metyrapone was linked with respiratory failure, deep vein thrombosis, interstitial lung disease, liver function test abnormal, and respiratory distress. Among osilodrostat-treated patients, those aged between 18 to 65 years old were more likely to develop adrenal insufficiency, fatigue, tachycardia, than those older than 65. Male patients treated with metyrapone have the significantly higher incidence of the increased blood corticotrophin, muscular weakness and acute respiratory distress syndrome compared to females. During treatment with osilodrostat and metyrapone, clinicians need to monitor the effects of AEs varied by gender and age and to pay more attention to new AE signals.
Keywords: osilodrostat; metyrapone; adverse events; disproportionality analysis